Long‐term outcomes of patients with hepatitis B virus‐related acute on chronic liver failure: An observational cohort study. (8th March 2019) - Lin, Su; Zhang, Kai; Zhang, Junchao; Wang, Mingfang; Velani, Bharat; Zhu, Yueyong
Abstract: Background and Aims: The long‐term outcomes of patients with hepatitis B virus‐related acute on chronic liver failure (HBV‐ACLF) remain unclear. The main aim of the study was to compare the 5‐year survival rate and incidence rate of hepatocellular carcinoma (HCC) between patients with HBV‐ACLF and HBV‐cirrhosis. Methods: Clinical data of patients with ACLF, compensated cirrhosis and decompensated cirrhosis who survived more than 3 months after diagnosis were collected. The survival rate and cumulative incidence of HCC were compared. The Cox regression was used to evaluate risk factors for outcomes. Results: A total of 814 patients were included in the analysis, including 122 (14.99%) patients with ACLF, 450 (55.28%) patients with compensated cirrhosis and 242 (29.73%) patients with decompensated cirrhosis. The 5‐year survival rate of patients with ACLF (97.2%) was higher than patients with decompensated cirrhosis (86.0%), but was lower than patients with compensated cirrhosis (99.1%). The 5‐year HCC incidence rate was the highest in the decompensated cirrhosis group (14.6%, P < 0.05), while no statistical differences were found between patients with ACLF (3.5%) and compensated cirrhosis (9.5%). The episode of ACLF did not increase the risk of HCC and the overall survival when compared with patients with cirrhosis. In ACLF subgroup analysis, the age, rather than the presence of cirrhosis, was independently associated with both mortality and incidence of HCC. Conclusions: ACLF patients who survived the first 3 months had a better long‐term prognosis than decompensated cirrhosis, while the HCC risk was comparable to compensated cirrhosis. HCC surveillance is strongly recommended for these patients.